KEPUASAN HIDUP MAHASISWA TINGKAT PERTAMA: KAITANNYA DENGAN KARAKTER MAHASISWA DAN GAYA PENGASUHAN ORANG TUA - Novianti, Dyanza Sri; ., Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
The first-grade college students who were living in the dormitory face transitional period toward the adult period. Therefore, it needed the ability to measure his life satisfaction. This study aimed 1) to analyze the differences between maternal and paternal parenting styles; 2) to analyze the influence of college student characteristic, family characteristic and parenting style toward college student character; and 3) to analyze the influence of college student characteristic, family characteristic, parenting style, and character toward life satisfaction. This research was conducted in Bogor Agricultural University, Bogor City, West Java Province. The sample consists of 102 first-grade college student which selected by multistage random sampling method. Maternal and paternal parenting styles perceived by students are measured using the Parent as Social Context Questionnaire (PASCQ-final version) instrument of Skinner, Sandy, and Tatiana (2005). College student characters are measured using the Value in Action Inventory of Strengths (VIA-IS) instrument. Meanwhile, life satisfaction was measured using an instrument developed by West (2006). Independent sample t-test found that there was a significant difference between maternal and paternal parenting styles on the warmth dimension. Regression analysis found that parenting style had a significant positive effect toward college student character. Regression analysis also found that character had a significant positive effect toward life satisfaction of college student.